Relationship Of Family Factor Againts The Development Of Children Age 4-6 Years Old In Padang Manis Village Wonosobo District Tanggamus Regency - Andrian Reza Saputra; Dian Isti angraini; Tri Umiana Soleha (CV. Jasa Sukses Abadi, 2019)
The family is the first environment that is introduced to the children. The family is the first subject that matter to be a factor of developmental deviation. This study’s aim to determine the relationship between Family Factors and children developmental in age 4-6 years old. Total samples of 52 family in Padang Manis village who selected with total sampling technique. Inclusion criteria is a family and child 4-6 year old who is willing to be a respondent. The results showed that there was a significant correlation between family income and children development with p = 0,003 (p <0,05). There was a significant correlation between parenting system and children development with p value = 0,034 (p <0,05). There was a significant relationship between parent educational background and children development with p = 0,001 (p <0,05). There was a significant relationship between the number of siblings and the development of children with a value of p = 0.001 (p <0.05). Result showed there is a relationship of family factors to the development of children in age 4-6 years old in the Padang Manis village Wonosobo district Tanggamus regency.